Plant-derived nanoparticles as alternative therapy against Diarrheal pathogens in the era of antimicrobial resistance: A review - Abolarinwa, Tesleem Olatunde; Ajose, Daniel Jesuwenu; Oluwarinde, Bukola Opeyemi; Fri, Justine; Montso, Kotsoana Peter; Fayemi, Omolola Esther; Aremu, Adeyemi Oladapo; Ateba, Collins Njie (Frontiers in Microbiology, 2022)
Diarrhoea is a condition in which faeces is discharged from the bowels frequently and in a liquid form. It is one of the frequent causes of morbidity and mortality in developing countries. The impact of diarrhoea is worsened by the increasing incidence of antimicrobial resistance among the causative agents, and this is now categorized as a global healthcare challenge. Antimicrobial resistance among diarrhoeal pathogens also contributes to extended infection durations, and huge economic loss even in countries with advanced public health policies. The ever-increasing incidence of antimicrobial resistance including the contraindications arising from the administration of antibiotics in some diarrhoeal cases highlights a crucial need for the development of novel non-antibiotic alternative agents for therapeutic and biocontrol applications. One such intervention includes the application of plant-derived nanoparticles (PDNPs) with novel antimicrobial properties. Given their small size and large surface area to volume ratio, PDNPs can attack target bacterial cell walls to generate reactive oxygen species that may simultaneously disrupt bacteria cell components such as DNA and proteins leading to cell damage or death. This potential can make it very difficult for pathogenic organisms to develop resistance against these antibacterial agents. In this review, we provide a critical overview on the antimicrobial resistance crisis among diarrhoeagenic bacteria. We also discuss the evidence from the existing literature to support the potential associated with the use of PDNPs as alternative therapeutic agents for multidrug resistant and antibiotics administer contraindicated bacteria that are associated with diarrhoea.